PENGARUH KEMAMPUAN MANAJERIAL DAN BUDAYA ORGANISASI TERHADAP MOTIVASI KERJA DAN KEPUASAN KERJA PEGAWAI RUMAH SAKIT UMUM DAERAH KABUPATEN ROKAN HULU - Mulya, Fitra; Zulfadil, Zulfadil (Jurnal Tepak Manajemen Bisnis, 2016)
This study aims to determine and analyze the Influence of Managerial Ability andCultural Organization Work Motivation and Job Satisfaction Employee Regional GeneralHospital Rokan Hulu.The method used in this research is quantitative. The types and sources ofdata in this study are primary data obtained from the results of empirical research bydistributing questionnaires to employees sampled. The analysis technique used is multiple linearregression.The results showed that (1) the ability of managerial partially significant effect onemployee motivation Regional General Hospital (Hospital) Rokan Hulu and have a positiveeffect on work motivation or unidirectional. (2) Cultural organizations are partially significanteffect on employee motivation Regional General Hospital (Hospital) Rokan Hulu and have apositive effect on work motivation or unidirectional. (3) The ability of managerial partially noeffect on employee satisfaction Regional General Hospital (Hospital) Rokan Hulu and have anegative impact on job satisfaction or upside down. (4) The organizational culture is partiallysignificant effect on employee satisfaction Regional General Hospital (Hospital) Rokan Huluand have a positive effect on job satisfaction or unidirectional. (5) Factors working motivationpartially significant effect on employee satisfaction Regional General Hospital (Hospital) RokanHulu and have a positive effect on job satisfaction or unidirectional. This means that, dependingon the level of employee satisfaction than the level of employee motivation is concerned. Thebetter the motivation to work, the better employee satisfaction.